Synthesis of ferroceramics for electromagnetic shock waves generators by vacuum aerosol deposition method - Rezinkin, O. L.; Rezinkina, M. M.; Gryb, O. G. (STC "Institute for Single Crystals", 2016)
Experimental bench and regimes of aerosol deposition at room temperature in vacuum of the fine grained ferroelectric layers with thickness of several hundred microns (the grains' size is less than 1 μm) and general formula BaO-SrO-TiO2 have been described. The results of experimental investigations of electrical physical characteristics of the obtained samples have been presented. It is shown that electric breakdown strength of the obtained ferroelectric layers exceeds in 1.4-2.5 times the electric breakdown strength of the similar samples made by the hot synthesis technology.
Синтез сегнетокераміки для електромагнітних генераторів ударних хвиль за допомогою вакуумного аерозольного напилювання
Keywords: ferroelectric ceramics; room temperature; impact consolidation; electric strength; non-linear electrical properties; pulse generators; currents; voltages